1996
DOI: 10.1007/bf02347787
|View full text |Cite
|
Sign up to set email alerts
|

Topographic variations of soil properties and stand structure in a Pinus thunbergii plantation

Abstract: Soil properties and above-and belowground forest structure were studied across various topographies in a 20-year-old Pinus thunbergii Parl. plantation on Mt Tanakami, Japan. The soil properties and stand structure varied greatly with slope position from ridge top to valley floor. Soil thickness, fine soil content and soil moisture content were greater in lower slope positions. The amount of organic carbon in the forest floor was greater in upper slope positions. The organic carbon content in the mineral soil w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 16 publications
4
59
0
Order By: Relevance
“…SWC was significantly lower in the UP than in the LP. Lower SWC was also observed in upper slope in previous studies Enoki et al, 1996;Tamai 2010 . Generally, the soil water content decreases upslope because of hydrological processes.…”
Section: Differences In Environmental and Biological Factorssupporting
confidence: 83%
See 2 more Smart Citations
“…SWC was significantly lower in the UP than in the LP. Lower SWC was also observed in upper slope in previous studies Enoki et al, 1996;Tamai 2010 . Generally, the soil water content decreases upslope because of hydrological processes.…”
Section: Differences In Environmental and Biological Factorssupporting
confidence: 83%
“…The multiple linear regression results showed that fine root biomass accounted for the additional spatial variation in R soil that was not explained by SWC and T soil , because AIC and R 2 of the best-fit model including fine rot biomass as an explanatory factor was better for other models without fine root biomass. Fine root biomass often determines the heterogeneity in R soil Katayama et al, 2009;Shibistova et al, 2002 , and fine root biomass often differs with slope position Enoki et al, 1996;Tateno et al, 2004 . Thus, fine root biomass played an important role in understanding the heterogeneity in R soil on a slope.…”
Section: Effect Of Environmental and Biological Factors On R Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Previous studies showed that the soil C/N ratio decreased from the upper to lower slope (Enoki et al 1996;Tateno and Takeda 2003) and a higher soil C/N ratio was found on the ridge (Enoki et al 1996). The high soil C/N ratio in the OKU6 indicates the soil condition of the site is dry enough even at the lower altitude, indicating that the shape of the relief, i.e., concave or convex, was more important than the altitude along the slope.…”
Section: Soil Propertiesmentioning
confidence: 93%
“…Previous studies have shown that stem productivity or height growth (site index) in Japanese forests is related to topography (Enoki et al 1996;Tateno and Takeda 2003;Zushi 2006) and soil type (Inoue et al 1973;Mashimo 1960). These studies suggest that soil water and nitrogen availability are the primary factors that determine stem productivity.…”
Section: Introductionmentioning
confidence: 99%